Try this:
1. sum of numbers is x+y=67, the difference between them is x-y=11
2. it is possible to make up and resolve the system:
Answer:
C
Step-by-step explanation:
In division when bases are same you do top exponent minus bottom exponent.
So here you do t^(12-6) which is t^6.
Answer:
Yes because the answer to both of them is 1
Step-by-step explanation:
Let's solve your equation step-by-step.
−2x+9=7
Step 1: Subtract 9 from both sides.
−2x+9−9=7−9
−2x=−2
Step 2: Divide both sides by -2.
−2x
−2
=
−2
−2
x=1
Answer:
x=1
Let's solve your equation step-by-step.
2x=2
Step 1: Divide both sides by 2.
2x
2
=
2
2
x=1
Answer:
x=1
Answer:
3x^2 -4
Step-by-step explanation:
F(x)=2x^2+3 and g(x)=x^2-7
(f+g)(x) =
We add the two functions together
(f+g)(x) =2x^2+3+x^2-7
I like to line them up vertically
(f+g)(x) =
2x^2 +3
+x^2 -7
------------------
3x^2 -4